(untitled) (Fiep Bulletin - online, 2012)
This study is characterized as a descriptive study whose objective was to analyze the profile of Stress and its relationship with the PA servers Federal Institute of Para As a focus aimed at identifying the level of stress and pressure of the servers and relate them. The study sample consisted of twenty-four (N = 24) of the Federal Institute servers, and in relation to gender, we used both. As an instrument of measurement, we used a anmenese (1989), protocol through the questionnaire Why Managers Burn Out, and the data were collected on the campus of Altamira / PA. As the result, since the stress level was presented as normal predominance of about 63% since the beginning was marked with about 33% and the stress was already installed with 4% and for PA-characterized with some 80% normal and high normal BP, which is characterized in "<130 to <85 and 130-139 in 85 to 89", now with 20% with hypertension level I, the protocol recommended by the Joint National Committee on Detecion, Evolution Hight Pressure and Treatment (1993). The study was conducted between September-October 2011. From the results, and using descriptive statistics, we got the following results: the features. BP servers by 80% normal and 20% level I hypertension Stress was characterized as the 63% that features about 15 servers without stress, as 33% that features about 8 servers with early stress and 4% with stress. When does the relationship between stress and BP notes that the balance as a percentage the same servers that have good results in both evaluations, characterizing that when the stress level was also being controlled pressure, we conclude that servers that regular physical activity had better results.